Ghana’s Fertiliser Subsidy Programme: Assessing Farmer Participation and Perceptions of its Effectiveness - Benjamin Tetteh Anang; Solace Kudadze (Universitas Andalas, 2019)
In 2008, the Government of Ghana introduced a national fertiliser subsidy programme to promote the production of cereals in the country. Documented evidence of the impact of the programme, factors affecting participation, and the perceptions of farmers about its effectiveness remains scanty and hard to find. This study therefore sought to investigate the factors affecting participation in the subsidy programme as well as farmers’ perceptions about its effectiveness using data from a cross-section of 300 farm households in northern Ghana. The study employed a probit model to assess the factors affecting participation in the subsidy programme while descriptive statistics were used to present the findings on farmers’ perceptions. The results indicated that participation in the subsidy programme is significantly influenced by educational status and farming experience of the household head, contact with agricultural extension agents, herd size, degree of specialisation in rice production, use of farm mechanisation and location of the farm. Furthermore, farmers perceived the subsidy programme to be ineffective in terms of timeliness, availability and distribution of subsidised fertiliser, access to coupons (vouchers), and distance to fertiliser depots. The findings underscore the need to ensure adequate and timely supply of subsidised fertiliser, improve communication on the availability of both fertiliser coupons and subsidised fertiliser, as well as increase in the number of extension workers to enhance the effectiveness of the subsidy programme.